Association of Gestational Diabetes Mellitus with Multi Drug Resistant Vaginal Infections among Pregnant Women - Tariq, Nida; Iqbal, Maryam; Sheraz, Mehwish; Rusho, Maher Ali; Naz, Saira; Musa, Bilal; Hameed, Usama; Khalid, Maryam (Indus Journal of Bioscience Research, 2025)
Background: Vaginal infections caused by various pathogenic microorganisms, along with the emergence of antibiotic resistance, pose significant medical challenges. Gestational diabetes mellitus (GDM) is a critical factor that can delay recovery from infections and lead to complications. Methodology: This study was conducted as a cross-sectional analysis involving pregnant women. A total of 120 vaginal swabs were collected from participants and analyzed to identify the microorganisms present and assess their antibiotic susceptibility. The subjects were categorized into two groups based on their diabetic status: those with GDM and those without. Various biochemical tests, culturing methods, and sensitivity patterns were performed on high vaginal swab isolates. Results: The analysis revealed that 56% of the women studied were aged between 23 and 37 years, with 67% in their third trimester. Among the microorganisms identified, Candida species accounted for 51%, while gram-positive bacteria comprised 24.3% and gram-negative bacteria 25.19%. Within the gram-positive category, Methicillin-resistant Staphylococcus aureus (MRSA) was the most prevalent at 30.25%, followed by Enterococcus faecalis at 15% and Streptococcus species at 3.11%. For gram-negative bacteria, Klebsiella pneumoniae was found in 44.4% of cases, E. coli in 31.3%, Pseudomonas aeruginosa in 14.1%, Pseudomonas stutzeri in 6.05%, and Acinetobacter baumannii in 3.02%. Susceptibility testing indicated that Staphylococcus aureus was primarily sensitive to Linezolid but resistant to azithromycin, while vancomycin and cotrimoxazole were most effective against MRSA, with cloxacillin showing significant resistance. Vancomycin was also the most effective treatment for E. faecalis, whereas azithromycin exhibited high resistance levels. Among gram-negative bacteria, Gentamicin was most effective against E. coli, while Rofloxacin showed the highest resistance; Imipenem was most effective against P. aeruginosa, with Amikacin showing significant resistance. A significant association was found between multidrug-resistant (MDR) vaginal infections and GDM. Conclusion: The study concluded that there is no significant association between MDR vaginal infections and gestational diabetes mellitus among pregnant women.